Effects of mouthwash interventions on xerostomia and unstimulated whole saliva flow rate among hemodialysis patients: A randomized controlled study. (November 2016) - Yu, I-Chen; Tsai, Yun-Fang; Fang, Ji-Tseng; Yeh, Mei-Ming; Fang, Jia-You; Liu, Chieh-Yu
Abstract: Background: Dry mouth (xerostomia) is a common symptom in hemodialysis patients, which is associated with a reduced salivary flow. Xerostomia affects patients' oral health and quality of life. Objectives: The aim of this study was to investigate using a mouthwash as a means to reduce xerostomia and improve saliva flow rates in hemodialysis patients. Design: A randomized controlled trial. Settings and methods: Three dialysis centers in Northern Taiwan served as the study sites. Patients were purposively sampled from three hemodialysis centers in Taiwan and randomly assigned to one of three groups: pure water mouthwash; n = 41, licorice mouthwash; n = 44, or no mouthwash (control); n = 37. The Summated Xerostomia Inventory, and unstimulated whole salivary flow rate measured dry mouth and salivary flow, respectively. Data was collected at baseline, dialysis Day 5 and Day 10. Results: One hundred twenty-two patients participated in this study. Baselines were adjusted for any imbalances in variables and generalized estimating equations analysed the data. Compared to control, a pure water mouthwash resulted in an increase in the unstimulated salivary flow rate of 25.85 × 10 −3 mL/min and 25.78 × 10 −3 mL/min ( p < 0.05) at Day 5 and Day 10, respectively. The estimated effect size was 1.38. However, there was no significant decrease in Summated Xerostomia Inventory scores. The licorice mouthwash also significantly improved the unstimulated salivary flow rates to 114.92 × 10 −3 mL/min, and 131.61 × 10 −3 mL/min at Day 5 and Day 10, respectively ( p < 0.001). However, in contrast to the pure water mouthwash, the licorice mouthwash resulted in a significant improvement in the scores for the Summated Xerostomia Inventory ( p < 0.001). Conclusion: Although a pure water or a licorice mouthwash and improved the objective measure of salivary flow rate, only the licorice mouthwash provided subjective relief of xerostomia. This suggests the use of a licorice mouthwash may effectively relieve feelings of dry mouth in hemodialysis patients.